The Determinants of Financial Performance of South African State-Owned Entities - MARIMUTHU, Ferina; MVUNABANDI, Jean Damascene; MAAMA, Haruna (International Journal of Environmental, Sustainability, and Social Science, 2023)
Several state-owned enterprises (SOEs) have severally faced imminent collapse, resulting in various support from the government. This has increased the debt level of the government and the SOEs. The study examined the factors that influence the financial performance of South African SOEs. This study used a quantitative methodology and secondary data of 33 South African SOEs from 1995 to 2017. The data were analysed using a multiple regression model and the GMM estimation technique. The study's conclusions show a statistically significant inverse relationship between capital structure and financial performance. The evidence further showed that government intervention in financial assistance, such as grants, funds, rebates, and subsidies, has contributed to the poor performance of SOEs. The inverse association suggests that the SOEs performance continues to worsen despite government support, which is quite concerning. The results demonstrate that government support is not a sound choice for developing SOEs since it makes management more dependent on it to meet operational needs and seize expansion possibilities. Additionally, the increased use of debt stresses government finances due to the rise in government guarantees. The study concludes that, contrary to the agency theory, leverage does not enhance SOEs' performance, suggesting they should be careful when selecting their capital structure. Finally, the South African SOEs’ performance is being hampered by government support. The findings have several policy implications for the government and the management of SOEs.